A CASE OF ACROMEGALY COMPLICATED BY PRIMARY ALDOSTERONISM DIAGNOSED DURING THE COURSE OF HEART FAILURE. (April 2021) - Kimura, Miwa; Yamashita, Kaoru; Ishikawa, Toru; Saitou, Fumiko; Kimura, Shihori; Takano, Noriyoshi; Seki, Yasufumi; Masui, Kenta; Bokuda, Kanako; Sasaki, Nobukazu; Yatabe, Midori; Yatabe, Junichi; et al.
Abstract : Objective: [Case] A 32-year-old male was admitted to the Department of Cardiology of our hospital complaining of weight gain, exertional chest pain, dyspnea, and palpitation. He was pointed out hypertension at the age of 18 and started taking oral antihypertensive drugs at the age of 27. Although his high blood pressure was well-controlled with calcium channel blocker, angiotensin receptor blocker, and alpha-and beta-blocker, he had stopped taking medicines since the age of 30. He was diagnosed as congestive heart failure due to hypertensive heart disease and was transferred to our department for the further examination of suspected secondary hypertension after his heart failure was improved. Design and method: Aldosterone / renin activity ratio (ARR) was >= 200, and primary aldosteronism (PA) was suspected. In consideration of his impaired cardiac function, a captopril challenge test and a rapid ACTH stimulation test were conducted. Since both were positive, the diagnosis of PA was made. Although computed tomography (CT) scans revealed a left adrenal adenoma, adrenal venous sampling showed overproductions of aldosterone from both adrenal glands, and thus he was treated with eplerenone, a mineral corticoid receptor blocker. Results: He was also suspected to have acromegaly because he had protruded chin, thickened lips, enlarged nose, and enlarged hands and feet. Brain magnetic resonance (MR) imaging detected a macroadenoma in the pituitary gland. Endocrinological examinations showed high concentrations of serum GH of 7.78 ng/ml and insulin-like growth factor 1 (IGF-1) of 824 ng/ml (+8.8SD), and 75 g oral glucose tolerance test (OGTT) showed a nadir of GH as 5.22 ng/ml, indicating a failure of suppression of GH. Acromegaly was diagnosed and transsphenoidal sinus pituitary surgery was done after monthly intramuscular injections of octreotide 20 mg four times. Conclusions: [Discussion] We experienced a case of acromegaly complicated by PA diagnosed during the course of heart failure. Both acromegaly and PA may be involved in the development of heart failure, however, the combination of acromegaly and PA is rare. We will discuss Its pathophysiology with a literature review.